Efficient organic photovoltaics with improved charge extraction and high short-circuit current - Mohan, Minu; Nandal, Vikas; Paramadam, Sanish; Reddy, Kasala Prabhakar; Ramkumar, Sekar; Agarwal, Sumanshu; Gopinath, Chinnakonda S.; Nair, Pradeep R.; Namboothiry, Manoj A. G. (Journal of Physical Chemistry C, 2017)
Exciton generation, dissociation, free carrier transport, and charge extraction play an important role in the short-circuit current (J(sc)) and power conversion efficiency of an organic bulk heterojunction (BHJ) solar cell (SC). Here we study the impact of band offset at the interfacial layer and the morphology of active layer on the extraction of free carriers. The effects are evaluated on an inverted BHJ SC using zinc oxide (ZnO) as a buffer layer, prepared via two different methods: ZnO nanoparticle dispersed in mixed solvents (ZnO A) and sol-gel method (ZnO B). The device with ZnO A buffer layer improves the charge extraction and J(sc),. The improvement is due to the better band offset and morphology of the blend near the ZnO A/active layer interface. Further, the numerical analysis of current-voltage characteristics illustrates that the morphology at the ZnO A/active layer interface has a more dominant role in improving the performance of the organic photovoltaic than the band offset.